Using Drone‐Derived Imagery to Describe Prey Sharing Behaviors in Two Piscivorous Resident Killer Whale Populations - Sharon W. C. Kay; Lance G. Barrett‐Lennard; Brittany C. Visona‐Kelly; Marie‐Ana Mikus; Michael N. Weiss; Darren P. Croft; Valeria Vergara; Holly Fearnbach; John W. Durban; Chris T. Darimont (Marine Mammal Science, 2026)
Cooperative foraging occurs across diverse taxa and facilitates prey acquisition and social learning, particularly when prey is shared among group members. In Resident killer whales ( Orcinus orca ater ), prey sharing is central to how individuals acquire salmonid prey, yet current research has relied primarily on boat‐based observations. Using 10 years of drone‐based imagery, we examined prey sharing behaviors in two populations, endangered Southern Resident killer whales (SRKWs) and threatened Northern Resident killer whales (NRKWs). Our goal was to evaluate the utility of drones for documenting prey sharing behaviors and conduct preliminary comparisons between NRKW and SRKWs. We detected 41 NRKW and 52 SRKW predation events, with prey sharing observed in 24 NRKW (59%) and 22 SRKW (42%) events. Drones effectively documented prey sharing at or near the surface, revealing subtle behaviors and allowing us to track the roles of individuals. Initial comparisons revealed that adult female NRKWs shared prey more frequently than adult female SRKWs and shared larger portions of prey. Although preliminary, our findings suggest differences in prey sharing between the populations, possibly reflecting social or ecological differences. Overall, drone‐based methods provide valuable insights into foraging behavior in free‐ranging cetaceans and offer a new approach to investigate cooperative behaviors.

Using reflectance to measure chlorophyll a in corals: calibration and implications of skeletal optical properties - Kay Watty; Verena Schoepf; Kelly W. Johnson; Sophie Littke; Rene M. van der Zande (Coral Reefs, 2026)
Climate change-driven coral bleaching and associated chlorophyll (Chl) loss increasingly threaten coral reefs, highlighting the need for non-invasive, cost-effective tools to assess corals’ physiological condition. Researchers have explored the reflectance-based Normalized Difference Vegetation Index (NDVI) as a proxy for Chl a . However, almost no calibration curves exist to date; thus it remains unknown if the relationship between Chl a and NDVI differs among coral species, and whether it is influenced by skeletal optical properties. Here, we correlated Chl a content to NDVI in three coral species with different skeletal morphologies and reflectance modes across a range of health states (i.e., bleaching states). We found a strong positive relationship between Chl a and NDVI in all species, validating NDVI as a proxy for Chl a in corals. However, this relationship is non-linear, showing deviations at the highest and lowest ends of the pigmentation spectrum. We propose that in healthy states, this non-linearity is due to pigment self-shading, whereas in bleaching states, it is caused by backscattering of light by the increasingly exposed coral skeleton, because pigment loss enhances absorption by the remaining Chl a pigments and lowers, rather than increases, reflectance. To avoid Chl a under- or overestimation, we recommend to log-transform Chl a and create species-specific calibration curves. Overall, the non-invasive, repeatable, and scalable nature of reflectance measurements and NDVI make them valuable tools for assessing coral health both ex- and in situ. They provide a comprehensive view of the holobiont’s physiological condition and hold potential for broader applications in reef-scale monitoring, remote sensing, coral restoration, and conservation.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Assessment of filter subsampling and extrapolation for quantifying microplastics in environmental samples using Raman spectroscopy - Dounia El Khatib; Troy D. Langknecht; Michaela A. Cashman; Mark Reiss; Kelly Somers; Harry Allen; Kay T. Ho; Robert M. Burgess (Marine Pollution Bulletin, 2023)

A Near Four-Decade Time Series Shows the Hawaiian Islands Have Been Browning Since the 1980s - Austin Madson; Monica Dimson; Lucas Berio Fortini; Kapua Kawelo; Tamara Ticktin; Matt Keir; Chunyu Dong; Zhimin Ma; David W. Beilman; Kelly Kay; Jonathan Pando Ocón; Erica Gallerani; et al. (Environmental Management, 2023)
The Hawaiian Islands have been identified as a global biodiversity hotspot. We examine the Normalized Difference Vegetation Index (NDVI) using Climate Data Records products (0.05 × 0.05°) to identify significant differences in NDVI between neutral El Niño-Southern Oscillation years (1984, 2019) and significant long-term changes over the entire time series (1982–2019) for the Hawaiian Islands and six land cover classes. Overall, there has been a significant decline in NDVI (i.e., browning) across the Hawaiian Islands from 1982 to 2019 with the islands of Lāna’i and Hawai’i experiencing the greatest decreases in NDVI (≥44%). All land cover classes significantly decreased in NDVI for most months, especially during the wet season month of March. Native vegetation cover across all islands also experienced significant declines in NDVI, with the leeward, southwestern side of the island of Hawai’i experiencing the greatest declines. The long-term trends in the annual total precipitation and annual mean Palmer Drought Severity Index (PDSI) for 1982–2019 on the Hawaiian Islands show significant concurrent declines. Primarily positive correlations between the native ecosystem NDVI and precipitation imply that significant decreases in precipitation may exacerbate the decrease in NDVI of native ecosystems. NDVI-PDSI correlations were primarily negative on the windward side of the islands and positive on the leeward sides, suggesting a higher sensitivity to drought for leeward native ecosystems. Multi-decadal time series and spatially explicit data for native landscapes provide natural resource managers with long-term trends and monthly changes associated with vegetation health and stability.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Catalytic linkage between caspase activity and proteostasis in Archaea - Mansha Seth‐Pasricha; Stefan Senn; Laura E. Sanman; Matthew Bogyo; Vikas Nanda; Kelly A. Bidle; Kay D. Bidle (Environmental Microbiology, 2019)
Summary The model haloarchaeon, Haloferax volcanii possess an extremely high, and highly specific, basal caspase activity in exponentially growing cells that closely resembles caspase‐4. This activity is specifically inhibited by the pan‐caspase inhibitor, z‐VAD‐FMK, and has no cross‐reactivity with other known protease families. Although it is one of the dominant cellular proteolytic activities in exponentially growing H. volcanii cells, the interactive cellular roles remain unknown and the protein(s) responsible for this activity remain elusive. Here, biochemical purification and in situ trapping with caspase targeted covalent inhibitors combined with genome‐enabled proteomics, structural analysis, targeted gene knockouts and treatment with canavanine demonstrated a catalytic linkage between caspase activity and thermosomes, proteasomes and cdc48b, a cell division protein and proteasomal degradation facilitating ATPase, as part of an ‘interactase’ of stress‐related protein complexes with an established link to the unfolded protein response (UPR). Our findings provide novel cellular and biochemical context for the observed caspase activity in Archaea and add new insight to understanding the role of this activity, implicating their possible role in the establishment of protein stress and ER associated degradation pathways in Eukarya .

High‐resolution sequencing reveals unexplored archaeal diversity in freshwater wetland soils - Adrienne B. Narrowe; Jordan C. Angle; Rebecca A. Daly; Kay C. Stefanik; Kelly C. Wrighton; Christopher S. Miller (Environmental Microbiology, 2017)
Summary Despite being key contributors to biogeochemical processes, archaea are frequently outnumbered by bacteria, and consequently are underrepresented in combined molecular surveys. Here, we demonstrate an approach to concurrently survey the archaea alongside the bacteria with high‐resolution 16S rRNA gene sequencing, linking these community data to geochemical parameters. We applied this integrated analysis to hydric soils sampled across a model methane‐emitting freshwater wetland. Geochemical profiles, archaeal communities, and bacterial communities were independently correlated with soil depth and water cover. Centimeters of soil depth and corresponding geochemical shifts consistently affected microbial community structure more than hundreds of meters of lateral distance. Methanogens with diverse metabolisms were detected across the wetland, but displayed surprising OTU‐level partitioning by depth. Candidatus Methanoperedens spp. archaea thought to perform anaerobic oxidation of methane linked to iron reduction were abundant. Domain‐specific sequencing also revealed unexpectedly diverse non‐methane‐cycling archaeal members. OTUs within the underexplored Woesearchaeota and Bathyarchaeota were prevalent across the wetland, with subgroups and individual OTUs exhibiting distinct occupancy and abundance distributions aligned with environmental gradients. This study adds to our understanding of ecological range for key archaeal taxa in a model freshwater wetland, and links these taxa and individual OTUs to hypotheses about processes governing biogeochemical cycling.

A non-canonical role for desmoglein-2 in endothelial cells: implications for neoangiogenesis - Lisa M. Ebert; Lih Y. Tan; M. Zahied Johan; Kay Khine Myo Min; Michaelia P. Cockshell; Kate A. Parham; Kelly L. Betterman; Paceman Szeto; Samantha Boyle; Lokugan Silva; Angela Peng; YouFang Zhang; et al. (Angiogenesis, 2016)

The opioid receptor pharmacology of GSK1521498 compared to other ligands with differential effects on compulsive reward-related behaviours - Eamonn Kelly; Stuart J. Mundell; Anna Sava; Adelheid L. Roth; Antonio Felici; Kay Maltby; Pradeep J. Nathan; Edward T. Bullmore; Graeme Henderson (Psychopharmacology, 2015)

Seasonal reliance on nectar by an insectivorous bat revealed by stable isotopes - Winifred F. Frick; J. Ryan Shipley; Jeffrey F. Kelly; Paul A. Heady; Kathleen M. Kay (Oecologia, 2014)

Tantalizing evidence for caspase‐like protein expression and activity in the cellular stress response of Archaea - Kelly A. Bidle; Liti Haramaty; Natalie Baggett; Jennifer Nannen; Kay D. Bidle (Environmental Microbiology, 2010)
Summary An enigmatic feature of microbial evolution is the emergence of programmed cell death (PCD), a genetically controlled form of cell suicide triggered by environmental stimuli. Archaea , the second major prokaryotic domain of life, have been notably absent from the PCD inheritance discussion, due to a lack of genetic homologues. Using the model haloarchaeon Haloferax volcanii , we document extremely high caspase‐specific activity and expression of immunoreactive proteins to human caspase 8 antisera, both of which were induced by salt stress and death and were abolished by in vivo addition of a broad‐spectrum caspase inhibitor. Caspase inhibition severely impaired cell growth under low and high salt stress, demonstrating a critical role in the cellular stress response. In silico analysis of the H. volcanii proteome identified a subset of 18 potential target proteins containing a signature tetrapeptide caspase cleavage motif (IETD), some with putative roles in allosteric regulation, signal transduction, osmotic stress and cell communication. Detection of similarly high activity and expression in other haloarchaea ( Halorubrum and Haloarcula ) and in diverse members of Euryarchaeota (the methanogen Methanosarcina acetivorans and the hyperthermophile Pyrococcus furiosus ) and Crenarchaeota (the acidophile Sulfolobus solfataricus ) argue for a broad representation within the archaeal domain. By playing a role in normal cell function, caspase‐like proteases in Archaea appear to have co‐evolved with other metabolic pathways, broadening their biological roles beyond apoptosis and cell death.